Micro-scale H2–CO2 Dynamics in a Hydrogenotrophic Methanogenic Membrane Reactor - Garcia-Robledo, Emilio; Ottosen, Lars D. M.; Voigt, Niels V.; Kofoed, M. W.; Revsbech, Niels P. (Frontiers in Microbiology, 2016)
Biogas production is a key factor in a sustainable energy supply. It is possible to get biogas with very high methane content if the biogas reactors are supplied with exogenous hydrogen, and one of the technologies for supplying hydrogen is through gas permeable membranes. In this study the activity and stratification of hydrogen consumption above such a membrane was investigated by use of microsensors for hydrogen and pH. A hydrogenotrophic methanogenic community that was able to consume the hydrogen flux within 0.5 mm of the membrane with specific rates of up to 30 m3 H2 m-3 day-1 developed within 3 days in fresh manure and was already established at time zero when analyzing slurry from a biogas plant. The hydrogen consumption was dependent on a simultaneous carbon dioxide supply and was inhibited when carbon dioxide depletion elevated the pH to 9.2. The activity was only partially restored when the carbon dioxide supply was resumed. Bioreactors supplied with hydrogen gas should thus be carefully monitored and either have the hydrogen supply disrupted or be supplemented with carbon dioxide when the pH rises to values about 9.